Biodegradable and plasma‐treated electrospun scaffolds coated with recombinant Olfactomedin‐like 3 for accelerating wound healing and tissue regeneration. Issue 6 (12th October 2016) - Dunn, Louise L.; de Valence, Sarra; Tille, Jean‐Christophe; Hammel, Philippe; Walpoth, Beat H.; Stocker, Roland; Imhof, Beat A.; Miljkovic‐Licina, Marijana
ABSTRACT: Three‐dimensional biomimetic scaffolds resembling the native extracellular matrix (ECM) are widely used in tissue engineering, however they often lack optimal bioactive cues needed for acceleration of cell proliferation, neovascularization, and tissue regeneration. In this study, the use of the ECM‐related protein Olfactomedin‐like 3 (Olfml3) demonstrates the importance and feasibility of fabricating efficient bioactive scaffolds without in vitro cell seeding prior to in vivo implantation. First, in vivo proangiogenic properties of Olfml3 were shown in a murine wound healing model by accelerated wound closure and a 1.4‐fold increase in wound vascularity. Second, subcutaneous implantation of tubular scaffolds coated with recombinant Olfml3 resulted in enhanced cell in‐growth and neovascularization compared with control scaffolds. Together, our data indicates the potential of Olfml3 to accelerate neovascularization during tissue regeneration by promoting endothelial cell proliferation and migration. This study provides a promising concept for the reconstruction of damaged tissue using affordable and effective bioactive scaffolds.